Class, consensus and repertoire at the Nottingham and Midland counties working classes industrial exhibition - Sutherland, Lucie (SAGE, 2010)
This article examines the aims and outcomes of the Nottingham and Midland Counties Working Classes Industrial Exhibition of 1865-1866, an event which ostensibly promoted the achievements of working class residents living in and around the [then] town of Nottingham. Here, the actual presence and the influence of these residents at the event will be charted, through close analysis of the place of the Exhibition within the town. Indeed, particular attention will be paid to the process by which the venue and its contents – including a versatile musical repertoire – were housed within a developing cultural quarter financed and approved by local government and industry leaders, a space that promoted rational cultural activity and modified contributions by individual exhibitors and performers, to produce an advertisement of stable civic identity.